SEIZURE OF PROPERTY IN CRIMINAL PROCEEDINGSAND THE CONSTITUTIONAL RIGHT OF OWNERSHIP (VERITAS LEGIS JOURNAL, 2026)
The author, an expert of the Constitutional Court of the Republic of Kazakhstan, examines the procedural and legal mechanism for seizing property in domestic criminal proceedings in the context of observing the constitutional right of persons who are not parties to criminal proceedings to property, as provided for in Article 26 of the Basic Law. The purpose of the work is to establish the prerequisites for concluding that the procedure established by the Criminal Procedure Code of the Republic of Kazakhstan (hereinafter referred to as the CPC) (Criminal Procedure Code, 2014) (Criminal Procedure Code, 2014) is inconsistent with subparagraph 4) of paragraph 3 of Article 77 of the Constitution of the Republic of Kazakhstan regarding the right of everyone to be heard in court. To achieve this goal, the following tasks were addressed: the degree of security of property rights of persons who are not parties to criminal proceedings, the nature of the violation of this right when considering the issue of seizing their property by a judge alone without holding a hearing. Attention is drawn to the special legal nature of the property seizure procedure, which is both a measure of criminal procedural coercion and a means of collecting evidence. Proposals are made to improve several provisions of the Criminal Procedure Code, including establishing a preventive seizure of property by the investigating judge for a reasonable period to prevent its loss, concealment, or intentional alienation. Until the final decision on the matter, a non-party to the proceedings will have the opportunity to prove directly in court that the seized property was acquired legally, not criminally, and was not used to conceal the proceeds of a crime.
Keywords: seizure of property; guarantees of property rights of persons who are not parties to criminal proceedings